Hacia una concepción autónoma de la responsabilidad precontractual y su aplicabilidad en el ordenamiento jurídico peruano - Morales Hervias, Rómulo Martín (2019)
The present paper proposes critical reflections to the prevailing thesis of Peruvian doctrine that considers that pre-contractual liability is subsumed in the general clause of atypical extra-contractual liability. In addition, a Peruvian judgment is analyzed to demonstrate that it is possible to argue in future cases the existence of a pre-contractual obligation based on the category of “an obligation without benefit”, which emanates from objective good faith.